The Molecular Basis of Human IgG-Mediated Enhancement of C4b-Binding Protein Recruitment to Group A Streptococcus - Ermert, David; Laabei, Maisem; Weckel, Antonin; Mörgelin, Matthias; Lundqvist, Martin; Björck, Lars; Ram, Sanjay; Linse, Sara; Blom, Anna M. (Frontiers in Immunology, 2019)
Streptococcus pyogenes infects over 700 million people worldwide annually. Immune evasion strategies employed by the bacteria include binding of the complement inhibitors, C4b-binding protein (C4BP) and Factor H in a human-specific manner. We recently showed that human IgG increased C4BP binding to the bacterial surface, which promoted streptococcal immune evasion and increased mortality in mice. We sought to identify how IgG promotes C4BP binding to Protein H, a member of the M protein family. Dimerization of Protein H is pivotal for enhanced binding to human C4BP. First, we illustrated that Protein H, IgG and C4BP formed a tripartite complex. Second, surface plasmon resonance revealed that Protein H binds IgG solely through Fc, but not Fab domains, and with high affinity (IgG-Protein H: KD=0.4 nM; IgG-Fc-Protein H: KD≤1.6 nM). Each IgG binds two Protein H molecules, while up to six molecules of Protein H bind one C4BP molecule. Third, interrupting Protein H dimerization either by raising temperature to 41°C or with a synthetic peptide prevented IgG-Protein H interactions. IgG Fc fragments or monoclonal human IgG permitted maximal C4BP binding when used at concentrations from 0.1 to 10 mg/ml. In contrast, pooled human IgG enhanced C4BP binding at concentrations up to 1 mg/ml; decreased C4BP binding at 10 mg/ml occurred probably because of Fab-streptococcal interactions at these high IgG concentrations. Taken together, our data show how S. pyogenes exploits human IgG to evade complement and enhance its virulence. Elucidation of this mechanism could aid design of new therapeutics against S. pyogenes.